PELATIHAN PERANCANGAN MEDIA PEMBELAJARAN INTERAKTIF ELEKTRONIK BERBASIS AUGMENTED REALITY (AR) BAGI GURU SMA DI DAERAH 3T - Irmawaty Natsir; Nurhayati Nurhayati; Novike Bela Sumanik (PAKEM: Jurnal Pengabdian Kepada Masyarakat, 2026)
This training activity is designed to improve the ability of Senior High School (SMA) teachers in the Frontier, Remote, and Disadvantaged (3T) areas in utilizing Augmented Reality (AR) technology as an electronic interactive learning media. The main objective of the training is to equip teachers with practical knowledge and skills in developing and using AR applications to create a more engaging and interactive learning experience for students. The training method includes theory sessions, demonstrations of the use of AR software, and direct practice in creating AR-based learning content for several subjects. The results of this activity indicate that teachers are more confident in integrating AR technology into the learning process, despite limited access and resources in the 3T areas. This training is expected to provide a positive contribution to improving the quality of education in the 3T areas and open up opportunities for teachers to explore innovative and adaptive teaching methods.